Relaxation dynamics of poly(vinylidene fluoride) studied by dynamical mechanical measurements and dielectric spectroscopy - Costa, C. M. (2012)
The aim of this study is to analyze the mobility of polymer chains in semicrystalline poly(vinylidene fluoride) (PVDF). PVDF crystallizes from the melt in the  crystalline phase. The transformation from the  phase to the electroactive  phase can be induced by stretching at temperatures in the range between 80 and 140 ºC. The spherulitic structure of the crystalline phase is deformed during stretching to form fibrils oriented in the direction of de strain. The amorphous phase confined among the crystalline lamellae is distorted as well and some degree of orientation of the polymer chains is expected. Dynamic-mechanical and dielectric spectroscopy measurements were performed in PVDF films stretched to strain ratios up to 5 at temperatures between 80 and 140 ºC. Dynamic-mechanical measurements were conducted between -60 ºC and melting and in this temperature range the relaxation spectra shows the main relaxation of the amorphous phase (called -relaxation) and at higher temperatures a relaxation related to crystallites motions (c-relaxation). Although the mean relaxation times of the -relaxation are nearly equal in PVDF before and after crystal phase transformation, a significant change of shape of the relaxation spectrum proves the effect of chain distortion due to crystal reorganization. In stretched PVDF the elastic modulus of the polymer in the direction of deformation is significantly higher than in the transversal one, as expected by chain and crystals fibril orientation. The recovery of the deformation when the sample is heated is related with the appearance of the c-relaxation. Dielectric spectroscopy spectrum shows the main relaxation of the amorphous phase and a secondary process (γ-relaxation) at lower temperatures. Stretching produce significant changes in the relaxation processes, mainly in the strength and shape of the main relaxation . The Havriliak-Negami function has been applied to analyze the dielectric response.